A New SNP-Based Genotyping Method for C. psittaci: Application to Field Samples for Quick Identification - Fabien Vorimore; Rachid Aaziz; Bertille de Barbeyrac; Olivia Peuchant; Monika Szymańska-Czerwińska; Björn Herrmann; Christiane Schnee; Karine Laroucau (Microorganisms, 2021)
Chlamydia (C.) psittaci is the causative agent of avian chlamydiosis and human psittacosis. In this study, we extracted single-nucleotide polymorphisms (SNPs) from the whole genome sequences of 55 C. psittaci strains and identified eight major lineages, most of which are host-related. A combined PCR/high-resolution melting (HRM) assay was developed to screen for eight phylogenetically informative SNPs related to the identified C. psittaci lineages. The PCR-HRM method was validated on 11 available reference strains and with a set of 118 field isolates. Overall, PCR-HRM clustering was consistent with previous genotyping data obtained by ompA and/or MLST analysis. The method was then applied to 28 C. psittaci-positive samples from animal or human cases. As expected, PCR-HRM typing results from human samples identified genotypes linked to ducks and pigeons, a common source of human exposure, but also to the poorly described Mat116-like genotype. The new genotyping method does not require time-consuming sequencing and allows a quick identification of the source of infection.